KINERJA SAHAM MENGGUNAKAN MEAN-VARIANCE ANALYSIS DALAM SIKLUS PEMULIHAN EKONOMI DI INDONESIA - Mohamad Samsul (Journal of Management and Business, 2005)
This study tried to know the performance difference that result from Treynor model, Sharpe model, Jensen model, and Treynor & Black model during the Indonesia's recovery period. The study takes 331 stock that listed in Jakarta Stock Exchange in last 2004. The data used are montly data of individual stock price index every end of the month from December 2002 till September 2005. The rate of SBI in normal condition was 1% per month used as risk free rate.Mean Variance Analysis used in this study, regarding to the 4 models above. Monthly average return calculated for each stock, then averaging for 33 months. The formula of the 4 models adjusted from mutual fund study to individual stock study. The hypothesis is there is difference of stock performance between Treynor model, Sharpe model, Jensen model, and Treynor and Black model in Indonesia's recovery period.The result shows that Treynor model and Sharpe model gives 148 or 45% stocks have average 3% return, and this is above the market return. Jensen and Treynor and Black model gives 138 or 42% stocks have return above the market. Treynor model and Sharpe model give 225 or 68 % stocks are undervalued, wether the Jensen model and Treynor and Black resulting 169 and 170 or 51% stocks are undervalued. Monthly return rate each stock is 6,1% (Treynor model and Sharpe model) and 7,3% (Jensen and Treynor and Black model). The statistics show that the return from these model are not significantly different (in 5%o error) for all undervalued stocks. But if performance measurement use return base on stock's preferencial in each model, then Jensen model has significant higher return in the same sample (equal or less than 75 sample). The benefit of these 4 model are to make stock's rating and then choose which stocks are the portofolio.